2021
DOI: 10.1016/j.esmoop.2021.100106
|View full text |Cite
|
Sign up to set email alerts
|

Combining immunotherapy with an epidrug in squamous cell carcinomas of different locations: rationale and design of the PEVO basket trial

Abstract: Squamous cell carcinomas (SCCs) are among the most frequent solid tumors in humans. SCCs, related or not to the human papillomavirus, share common molecular features. Immunotherapies, and specifically immune checkpoint inhibitors, have been shown to improve overall survival in multiple cancer types, including SCCs. However, only a minority of patients experience a durable response with immunotherapy. Epigenetic modulation plays a major role in escaping tumor immunosurveillance and confers resistance to immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Further studies are needed to confirm the clinical value of HPV ctDNA for an early detection of residual disease/relapse and to evaluate the role/purpose of salvage surgery as compared with that of innovative drug combinations for patients with residual HPV ctDNA after treatment. Two studies, Circa HPV (NCT03739775) and the PEVO basket trial (NCT04357873), are actually ongoing and will allow a comparison between imaging and HPV ctDNA and evaluate its predictive value for relapse detection and for efficacy of innovative drug combination ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to confirm the clinical value of HPV ctDNA for an early detection of residual disease/relapse and to evaluate the role/purpose of salvage surgery as compared with that of innovative drug combinations for patients with residual HPV ctDNA after treatment. Two studies, Circa HPV (NCT03739775) and the PEVO basket trial (NCT04357873), are actually ongoing and will allow a comparison between imaging and HPV ctDNA and evaluate its predictive value for relapse detection and for efficacy of innovative drug combination ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beside the combination of two immunotherapy agents, or combination with chemotherapy or targeted therapies already approved in the treatment of HNSCC, another strategy is to assess the effect of epidrugs (epigenetic enzyme inhibitors), like vorinostat, a Histone DesACetylases (HDAC) inhibitor in combination with immune checkpoint inhibitors, as preclinical evidence has suggested that modulating the epigenome might modulate antitumor response and improve the efficacy of current immunotherapies (NCT04357873) (Table 5.2) [22].…”
Section: Combination Of Anti-immune Checkpoint Moabs With Other Type ...mentioning
confidence: 99%
“…PEVO trial evaluates the response to the combination of pembrolizumab and vorinostat, HDAC inhibitor, in several tumors recurrent and metastatic squamous cell carcinomas, HPV+ vs. HPV−. This study might provide clues to determine how HPV presence influences tumors’ therapeutic response and could also identify predictive and pharmacodynamic biomarkers ( de Guillebon et al, 2021 ).…”
Section: Epigenetic Therapy and Chemopreventionmentioning
confidence: 99%